Seleção de fungos filamentosos com atividade amilolítica - Oliveira, Ana Carolina Glória de [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
Amylases are enzymes that hydrolyze a carbohydrate reserve, starch. Starch is a high molecular weight glucose polymer found in many plants as a major source of nutritional reserve, and provides 70-80% of the calories consumed by man. Several hydrolytic enzymes are capable of degrading the starch. Hydrolytic action breaks down as bonds in the starch molecule, reacting in the presence of water, resulting in a new non-reducing end. Such enzymes can be classified as amylases and transferases, which hydrolyze α-1,4-glycosidic bonds, and debranching amylases, those which hydrolyze α-1,6-glycosidic bonds. Considering the great microbial diversity in different national biomes, this work aimed to isolate fungal strains with potential in the production of amylolytic enzymes.The microorganisms studied in these trials were collected in the Amazon Biome area in the Bacia do Rio Teles Pires, located in the Paranaíta-MT city. The microorganisms were cultured using Plate Count Agar (PCA) with addition of chloramphenicol to inhibit bacterial growth. Solid - State Cultivation (SSC) were applied to enzymatic production assays, using wheat bran as a substrate. The fermentation process was carried out in Erlenmeyr flasks containing 5 g of substrate and 10 mL of saline solution. The flasks were inoculated with 5 disks of 0.5 cm diameter and it was transferred for incubator BOD type at 30 °C for 96 hours. After this period 50 mL of water was added to obtain the crude enzymatic solution. Amylolytic activity was determined by dextrinizing method proposed by PONSAWASDI; YAGISAWA (1987) and FUWA (1954). Five filamentous fungi stand out in amylase production, such as AC - 6.1, AC - 17.1, AC - 6.3, AC - 21.4 and AC - 21.3. These isolates shown mean amylase enzymatic of ± 105.24 U / mL

As amilases são enzimas que hidrolisam o carboidrato de reserva, amido. O amido é um polímero de glicose de alta massa molecular, encontrado em muitas plantas como a principal fonte de reserva nutricional, além de fornecer de 70 a 80% das calorias consumidas pelo homem. Várias enzimas hidrolíticas são capazes de degradar o amido, elas quebram as ligações na molécula do amido, reagindo em presença de água, resultando em uma nova extremidade não redutora. Tais enzimas podem ser classificadas em amilases transferases, que hidrolisam as ligações do tipo α-1,4, e amilases desramificantes, aquelas que hidrolisam as ligações do tipo α-1,6. Tendo em vista a grande diversidade microbiana em diferentes biomas nacionais, presente trabalho teve como objetivo isolar linhagens fungicas com potencial na produção de enzimas amilolíticas. Os microrganismos estudados nesse ensaio foram coletados em área do Bioma Amazônia na bacia do rio Teles Pires, localizada no município e Paraníta-MT. Os microrganismos foram cultivados utilizando Ágar Padrão para Contagem (PCA) com adição de cloranfenicol para inibir o crescimento bacteriano. Para os ensaios de produção enzimática foi adotada cultivo em estado sólido (CES), utilizando farelo de trigo como substrato. O processo fermentativo se deu em frascos Erlenmeyr contendo 5 g do substrato e 10 mL de solução salina, os quais foram inoculados com 5 disco de 0,5 cm diâmetro e incubados em estufa tipo BOD a 30 °C, por 96 horas. Após esse período foi adicionado 50 mL de água para obtenção da solução enzimática bruta. A determinação da atividade amilolítica foi realizada pelo método dextrinizante proposto por PONSAWASDI; YAGISAWA (1987) e FUWA (1954). Cinco isolados se destacaram na produção de amilase, sendo os isolados AC - 6.1, AC - 17.1, AC - 6.3, AC - 21.4 e AC - 21.3 com atividades enzimáticas média de ± 105,24 U/mL
Keywords: Microorganismos do solo; Biotecnologia microbiana; Fungos filamentosos; Filamentous fungi